MEMAKNAI YESUS DI TENGAH MASYARAKAT MEGAPOLITAN JAKARTA - Cornelius Iman Sukmana; Karinna Karinna Karinna (Jurnal Teologi (Journal of Theology), 2017)
Christian peoples in megapolitan Jakarta are ordinary citizens like others. They have similar problems for instance unemployment, corruption and transparency, environmental degradation, transportation and traffic jam, etc. City offers pleasure and luxury too, that can alienate one from oneself. Before these chalenges, citizens need a model, one who can be inspiring. For Christians, Jesus Christ is Lord, as well as a model that can be imitated. But in a megapolitan context, who can it be a real figure of inspiration? In this case, Governor Basuki Tjahaja Purnama or Ahok is an extraordinary local leader, and can be considered as a role model. His goverment is clean and strongly anti-corruption, transparent; his government is obviously administrating social justice. Character of a local leader that reflects the values of the Good News of Jesus Christ is indeed inspiring and can be followed as well imitated.